Laboratory Evaluation on Performance of Fiber-Modified Asphalt Mixtures Containing High Percentage of RAP - Yuefeng Zhu; Yanwei Li; Chundi Si; Xiaote Shi; Yaning Qiao; Haoran Li (Advances in Civil Engineering)
In recent years, the significant demand for sustainable paving materials has led to a rapid increase in the utilization of reclaimed asphalt pavement (RAP) materials. When RAP is mixed with virgin asphalt concrete, particularly when its percentage is high, performance of the binder and asphalt concrete can be adversely affected. For this reason, different types of additives need to be identified and evaluated beforehand to mitigate the adverse effects. In this study, different types of fiber materials were identified and selected as binder/mixture additives, including lignin fiber (LF), polyester fiber (PF), and basalt fiber (BF). Various samples of fiber-modified binders and asphalt mixtures with different RAP contents (0%, 20%, and 40%) were prepared and were evaluated using two sets of laboratory testing: (i) dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests were performed to study the rheological properties of fiber-modified binders; (ii) the wheel tracking test, bending creep test, moisture susceptibility test, fatigue test, and self-healing fatigue test were conducted to characterize the laboratory properties of fiber-modified RAP mixtures. Test results for the modified binders show that the BF-modified binder has the greatest positive effect on the high-temperature performance of the asphalt binder, followed by PF- and LF-modified binders. However, the virgin asphalt shows the best low-temperature property than the fiber-modified asphalt binder. Test results for the whole RAP mixtures show that all fibers have a significant effect on the properties (including high- and low-temperature stability, moisture susceptibility, fatigue, and self-healing ability) of RAP mixtures. Among them, adding BF shows the greatest improvement in high-temperature stability, fatigue resistance, and self-healing ability of RAP mixtures. LF is found to significantly enhance low-temperature properties, and PF can greatly improve the resistance to moisture damage of RAP mixtures. For high percentage of RAP using on sites, adding multiple additives may further enhance its durability.